The Implementation of Salaf, Tahfidz, and Modern Learning Methods in Enhancing the Understanding of Islamic Teachings at Al-Kamal Islamic Boarding School, Kebumen - Algi, Muhamad; Tajab, Muh.; Nuraini, Nuraini (ISTAWA, 2022)
The learning method is a stage of interaction between teachers and students to achieve learning objectives. The aim of this research is to determine the implementation of salaf, tahfdidz, and modern methods. Looking at the results and obstacles in implementing salaf, tahfdidz and modern methods in increasing understanding of Islamic religious education at the Al Kamal Islamic boarding school, Kebumen. This research uses a descriptive qualitative approach, with a field study type of research. We carried out this research at the Al Kamal Islamic boarding school, Kebumen, Central Java. Data collection techniques in this research were by conducting interviews, observation and documentation. With this method, you can obtain concrete data according to the needs of this research. Research results The results of the implementation of salaf, tahfidz and modern methods at the Al-Kamal Islamic boarding school can be seen from the very good understanding of the students. The students are able to instill Islamic values in everyday life. However, the implementation of these methods has obstacles in the application process, these obstacles are in learning foreign languages, Arabic or English, a form of modern methods that have not been fully implemented, this also conflicts with the Salaf method of studying classical books in Javanese.